Clinical study of scorpion sting envenomation - Sarthi, Manjunatha; A., Ashoka; A. C., Basavraj; T. K., Mahesh (International Journal of Contemporary Pediatrics, 2019)
Background: Scorpion stings are common in India. Presentation of scorpion sting may vary from localised pain at the site of the sting to life threatening condition. Systemic envenomation will even result in death among one third of the subjects. The present study was conducted to determine the clinical presentation, course, complications and outcomes of scorpion sting envenomation among children as they are sensitive to scorpion envenomation. Methods: 50 cases of scorpion sting, admitted to 2 hospitals, under JJMMC, Davangere for 1 year were included. A detailed clinical history followed by examination was done. Relevant investigations were also done. All the cases were monitored for complications and managed accordingly. Results: Maximum number of cases were noted in the age group of 1-3 years and 10-12 years. 58% of them were boys, 54% of the cases had red scorpion sting. Pain at the sting site, diaphoresis and restlessness were the most common presenting symptoms. The common signs noted were restlessness, cold extremities and tachycardia. Commonest complications were peripheral circulatory failure, pulmonary oedema, myocarditis and congestive cardiac failure. Majority of cases recovered without any sequelae. Conclusions: Present study we conclude that majority of the cases were among boys belonged to 1-3year age group. Red scorpion sting was common, and commonest presentation was pain and recovered without any sequelae.